Pro Windows 8.1 development with XAML and C# - Liberty, Jesse; Japikse, Philip; Galloway, Jon (Apress, 2014)
Windows 8.1 apps are revolutionizing development on the Windowsplatform. Fast, fluid, tactile and chrome-free, they provide a brand-new lookand feel for Windows users. These apps rely on Microsoft's Windows 8 modern UI to provide their rich andengaging user experiences for both desktop and tablet users. The new UI in turnrelies upon the Windows Runtime (WinRT) to give its apps unparalleledflexibility and power. Understanding this stack of new technologies and how they tie into the proven C# language and the XAML standard is the subject of this book. Experienced writers Jesse Liberty, Phil Japikse, and JonGalloway explain how you can get the most from Windows 8.1 byfocusing on the features that you need for your project and bringing yourexisting C# coding knowledge to bear. They begin with a nuts-and-bolts examination of how thetechnologies fit together and show you everything you need to get up andrunning with the new platform. Once you have a good understanding on thebasics, you progress to more advanced topics steadily increasing your understandingas a whole. This holistic knowledge is essential to truly master Windows 8.1development. Each topic is covered clearly and concisely and is packed with the details youneed to code effectively. The most important features are given a no-nonsense, in-depth treatment and chapters contain examples that demonstrate both thepower and the subtlety of Windows 8.1.